Additive for secondary batteries and lithium metal battery containing the same

By using ionic liquid composites with low standard reduction potential as additives in lithium metal batteries to form a protective layer, the problem of growth of lithium-core needle-shaped lithium and lithium dendrites is solved, the battery performance and life are improved, and safety risks are reduced.

JP2025511672AActive Publication Date: 2025-04-16LG ENERGY SOLUTION LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024558432
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2023-01-06
Publication Date
2025-04-16
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The existing lithium metal batteries have caused rapid growth of needle-shaped lithium and lithium dendrites due to the concentration of electric field of the lithium core and the concentration of lithium ion flow, resulting in a decline in battery performance and an increase in safety risks.

Method used

A new ionic liquid composite is used as a battery additive. The sodium ions of the additive have low standard reduction potential, which can form a protective layer for the lithium core, inhibit the concentrated flow of lithium ions, and reduce the growth of needle-shaped lithium and lithium dendrites.

Benefits of technology

By forming a uniform protective layer, the growth of needle-shaped lithium and lithium dendrites in the lithium core is effectively inhibited, the performance and life of lithium metal batteries are improved, and safety hazards are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511672000001_ABST
    Figure 2025511672000001_ABST
Patent Text Reader

Abstract

The present invention relates to an additive for secondary batteries that can suppress the growth of acicular lithium and induce uniform lithium growth on a thin lithium metal film to improve the performance and life of a lithium metal battery, and a lithium metal battery including the additive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0053361, filed on April 29, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to an additive for secondary batteries that can inhibit the growth of acicular lithium and induce uniform lithium growth on a lithium metal thin film, thereby improving the performance and lifespan of the lithium metal battery, and a lithium metal battery including the additive. [Background technology]

[0003] Lithium metal batteries use a thin film of lithium metal (Li-metal) as the negative electrode active material, and have the advantage of theoretically having a higher energy density and capacity (3860mAh g-1) than secondary batteries that use existing graphite-based negative electrodes. Therefore, research and development into lithium metal batteries is ongoing in order to apply them to secondary batteries that require high energy density.

[0004] However, lithium metal batteries have the drawback of causing large volume changes in the anode during charge / discharge due to the characteristics of lithium metal, which acts as the anode active material, and the needle-like lithium generated during charging grows to form lithium dendrites. If this lithium dendrite growth continues, it can penetrate the separator, causing an internal short circuit in the cell, which can cause serious problems with secondary battery performance and safety issues such as fire, and significantly reduces the lifespan of the secondary battery.

[0005] The growth of needle-like lithium and lithium dendrites on the lithium thin film is thought to occur because a stronger electric field is concentrated in the lithium tip formation area than in the flat area, causing the flow of lithium ions to concentrate at the protruding parts of the lithium tip during charge / discharge.

[0006] In particular, lithium metal, which serves as the negative electrode active material in lithium metal batteries, is highly reactive with electrolytes, which can lead to continuous irreversible reactions during charge and discharge. The rapid growth of acicular lithium and lithium dendrites due to these irreversible reactions can disrupt the solid electrolyte interphase (SEI) coating on the lithium metal thin film, further accelerating the irreversible reactions. As a result, continuous irreversible reactions and the growth of acicular lithium occur during the charge and discharge of lithium metal batteries, resulting in a rapid decline in the cell's capacity and performance, and a significant decrease in the lifespan and safety of the lithium metal battery.

[0007] Due to these problems of existing lithium metal batteries, research has been conducted from various angles on technologies to solve problems caused by the growth of needle-like lithium by forming a protective film on the lithium metal thin film, more specifically, on the lithium tip or protrusion, or by strengthening the solid electrolyte interfacial film.

[0008] One such technique has been proposed, which uses an ionic liquid compound, which exists in a liquid state containing cations and anions at the operating temperature of the battery, as an additive. The cations of the ionic liquid compound adsorb to the surface of the lithium chip to form a protective layer, thereby repelling lithium ions toward the periphery of the lithium chip. As a result, the concentration of lithium ions around the lithium chip or protrusion can be suppressed, thereby suppressing the rapid growth of acicular lithium or lithium dendrites and inducing uniform lithium growth. Therefore, it is known that the use of the ionic liquid compound as an additive can alleviate, to some extent, problems associated with the rapid growth of acicular lithium.

[0009] However, previously proposed ionic liquid compounds have a strong tendency to self-aggregate around lithium chips due to their high amphiphilicity, and as a result, the cations of the ionic liquid compounds cannot completely cover the lithium chips, resulting in the formation of an incomplete protective layer, which has been confirmed to still cause problems with the growth of acicular lithium or lithium dendrites.

[0010] Therefore, there is a continuing need for the development of technologies such as additives that can further reduce problems caused by the growth of acicular lithium or lithium dendrites in lithium metal batteries. Summary of the Invention [Problem to be solved by the invention]

[0011] Therefore, the present invention provides an additive for secondary batteries that can form a uniform protective layer around lithium chips, more effectively suppress the growth of acicular lithium, and induce uniform lithium growth on the lithium metal thin film, thereby improving the performance and lifespan of lithium metal batteries.

[0012] Another object of the present invention is to provide a lithium metal battery containing the additive in the electrolyte, which exhibits improved life characteristics and safety. [Means for solving the problem]

[0013] The present invention provides an additive containing an ionic liquid compound that exhibits a liquid state containing cations and anions at atmospheric pressure and a temperature of 100°C or less, and the cations are lithium cations (Li ) based on a standard hydrogen electrode (SHE). + ) and the cation has a symmetric structure with respect to the central element, with an even number of identical aliphatic hydrocarbon groups having 3 or more carbon atoms bonded to the central element.

[0014] In this secondary battery additive, the cation may have a standard reduction potential of -3.7 V to -3.1 V, -3.65 V to -3.15 V, or -3.6 V to -3.3 V versus the standard hydrogen electrode. Therefore, the cation is not substantially decomposed during charge / discharge and operation of a secondary battery such as a lithium metal battery, and may form an antilithium protective layer on the lithium metal thin film. In addition, cations with such low standard reduction potentials may preferentially adsorb over lithium ions to the surface of lithium chips in the lithium metal thin film, thereby forming a selective protective layer on the lithium chips.

[0015] In addition, the cation in the secondary battery additive has a self-diffusivity of 15*10 calculated by the Stejskal-Tanner equation using the analysis results of PFG-NMR (Pulsed Field Gradient-NMR). -11 m 2 .s -1 Or 30*10 -11 m 2 .s -1 , or 18*10 -11 m 2 .s -1 Or 28*10 -11 m 2 .s -1 , or 20*10 -11 m2 .s -1 Or 25*10 -11 m 2 .s -1 The hydrodynamic diameter calculated by the Stockes-Einstein equation using the PFG-NMR analysis results can be 1.5 to 3.0 nm, 1.8 to 2.8 nm, or 2.0 to 2.5 nm.

[0016] The self-diffusivity and hydrodynamic diameter of the additive can reflect its lower amphiphilicity, particularly its lower interaction with the non-aqueous organic solvent contained in the electrolyte, compared to additives with asymmetric cations, because the additive's cations have a symmetric structure consisting of multiple identical long-chain aliphatic hydrocarbon groups, e.g., long-chain linear alkyl groups. Therefore, the additive's cations have a lower tendency to self-aggregate around lithium chips or protrusions and can be uniformly adsorbed or bonded to the lithium chips to form a protective layer that selectively and uniformly surrounds the lithium chips. Therefore, the use of such an additive can more effectively suppress the growth of needle-shaped lithium or lithium dendrites from the lithium chips.

[0017] To enable the additive to exhibit such effects, the plurality of long-chain aliphatic hydrocarbon groups may be alkyl groups having 3 or more carbon atoms, or 3 to 20 carbon atoms, or 4 to 15 carbon atoms, or 5 to 10 carbon atoms, more suitably linear alkyl groups having such carbon numbers, and an even number of such hydrocarbon groups may be bonded to the central element of the cation, so that the cation has a symmetrical structure.

[0018] According to a specific example, the ionic liquid compound of the additive may be represented by the following Chemical Formula 1, and more specifically, may be represented by the following Chemical Formula 2:

[0019] [Chemical formula 1] [ka] In the above Chemical Formula 1, [ka] represents a nitrogen-containing heterocycle having 3 to 8 carbon atoms, or 4 to 7 carbon atoms, or 5 to 6 carbon atoms; the R1s each represent the same linear alkyl group having 3 to 20 carbon atoms, or 4 to 15 carbon atoms, or 5 to 10 carbon atoms; A - indicates an anion.

[0020] [Chemical formula 2] [ka]

[0021] In Formula 2, R1 represents the same linear alkyl group having 3 to 20 carbon atoms, or 4 to 15 carbon atoms, or 5 to 10 carbon atoms; A - indicates an anion.

[0022] The present invention also provides a lithium metal battery containing the additive. The lithium metal battery may include a negative electrode including a lithium metal thin film formed on a negative electrode current collector, an electrolyte including the additive, and a positive electrode including a positive electrode active material layer formed on a positive electrode current collector.

[0023] Such a lithium metal battery may further include a protective layer formed on the lithium metal thin film and containing the additive cations, and in the protective layer, the additive cations may be adsorbed or bound to the acicular lithium particles protruding from the lithium metal thin film so as to selectively cover the acicular lithium particles. [Effects of the Invention]

[0024] The additive of the present invention is an ionic liquid compound, and its cation has a low standard reduction potential, so it can adsorb more readily than lithium ions to the surface of a lithium metal negative electrode to form a protective layer. In particular, the additive can selectively form a protective layer on the lithium tip formation area where the flow of lithium ions concentrates during charge / discharge.

[0025] In addition, the cations of the additives have long-chain aliphatic hydrocarbon groups that are lithiophobic, which repel the lithium ions toward the periphery of the lithium chips, thereby suppressing the growth of acicular lithium or lithium dendrites from the lithium chips and allowing lithium to grow uniformly on the lithium metal anode.

[0026] Furthermore, the cationic structure of the additive exhibits relaxed amphiphilicity, which reduces the self-aggregation of the cations, thereby enabling selective formation of a uniform protective layer around the lithium chip and minimizing the occurrence of incomplete formation of the protective layer in some areas around the lithium chip.

[0027] Therefore, when the additive is used as an electrolyte additive to provide a secondary battery such as a lithium metal battery, the phenomenon of acicular lithium or lithium dendrite growing on the lithium metal negative electrode can be significantly reduced, and lithium can be grown uniformly on the lithium metal negative electrode during charge / discharge.

[0028] Therefore, such a lithium metal battery can minimize safety issues such as cell short circuit or fire due to the growth of the acicular lithium, and can exhibit significantly improved life characteristics by maintaining the high capacity characteristics unique to lithium metal batteries over the long term. [Brief explanation of the drawings]

[0029] [Figure 1]FIG. 1 is a diagram showing the technical principle by which the growth of needle-like lithium is suppressed and uniform lithium growth occurs when an additive (Pyr6(6)+) according to one embodiment of the invention is used, in comparison with the case where no additive is used and the case where a comparative additive (Pyr1(12)+) is used. [Figure 2a] Figure 2a shows electron microscope photographs of Comparative Example 1 (no additive used), Comparative Example 2 (using Pyr1(12)FSI additive), and Example 1 (using Pyr6(6)FSI additive) showing the growth of lithium by applying an electric charge to a lithium metal thin film, and a graph showing the number of lithium protuberances on each thin film, the average protuberance size, and the standard deviation. [Figure 2b] Figure 2b is an electron microscope photograph showing the growth of lithium by applying an electric charge to a lithium metal thin film for Comparative Example 1 (no additive used), Comparative Example 2 (using Pyr1(12)FSI additive), and Example 1 (using Pyr6(6)FSI additive), and is a graph showing the calculated number of lithium chips (protuberances) on each thin film, the average protuberance size, and the standard deviation. [Figure 2c] Figure 2c is an electron microscope photograph showing the growth of lithium by applying an electric charge to a lithium metal thin film for Comparative Example 1 (no additive used), Comparative Example 2 (using Pyr1(12)FSI additive), and Example 1 (using Pyr6(6)FSI additive), and is a graph showing the number of lithium protuberances on each thin film, the average protuberance size, and the standard deviation. DETAILED DESCRIPTION OF THE INVENTION

[0030] In this specification, when a part is said to "comprise" a certain element, this does not mean that it can further include other elements, unless otherwise specified. As used throughout this specification, terms of degree such as "about," "substantially," etc., are used to mean a numerical value or close to a numerical value when inherent manufacturing and material tolerances are given, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute numerical values ​​are recited for the purpose of understanding this application. As used throughout this specification, the terms "steps to" or "steps of" do not mean "steps for."

[0031] In this specification, the term "combination thereof" included in a Markush expression means a mixture or combination of one or more elements selected from the group consisting of elements described in the Markush expression, and means including one or more elements selected from the group consisting of the elements.

[0032] Based on the above definitions and the accompanying drawings, embodiments of the invention will now be described in detail, but these are given by way of example only and are not intended to limit the invention, which is defined only by the scope of the claims that follow.

[0033] FIG. 1 shows an example of an additive according to an embodiment of the present invention (Pyr6(6) + The technical principle behind the suppression of needle-like lithium growth and the more uniform lithium growth when using a Zn-containing additive is shown in the figure, compared to when no additive is used and when other additives are used.

[0034] According to one embodiment of the present invention, there is provided an additive comprising an ionic liquid compound that exhibits a liquid state containing cations and anions at atmospheric pressure and a temperature of 100°C or less, and the cations are lithium cations (Li ) based on a standard hydrogen electrode (SHE). + ) and the cation has a symmetric structure with respect to the central element, with an even number of identical aliphatic hydrocarbon groups having 3 or more carbon atoms bonded to the central element.

[0035] The additive of one embodiment is an ionic liquid compound that exhibits a liquid state containing cations and anions at the operating or charge / discharge temperature of the secondary battery, for example, atmospheric pressure (e.g., 1 atmosphere) and a temperature of 100°C or less, or 0 to 100°C, or 20 to 100°C, and can be effectively contained as an additive in an electrolyte of a lithium metal battery, for example, an electrolyte solution containing a lithium salt and a non-aqueous organic solvent.

[0036] In one embodiment, the cation of the additive is a lithium cation (Li ) based on a standard hydrogen electrode (SHE). + ) (approximately −3.04 V). Therefore, as shown in FIG. 1, when an electric field is concentrated around the lithium tip or protrusion during charge / discharge, the cations are preferentially reduced over lithium ions by the electric field and can bind or adsorb to the surface of the lithium metal negative electrode at the lithium tip formation portion. The long-chain aliphatic hydrocarbon groups bound to these cations are assembled to form a selective protective layer surrounding the lithium tip. Furthermore, due to the low standard reduction potential, the cations are not decomposed during charge / discharge and operation of a secondary battery such as a lithium metal battery, allowing the protective layer to be formed.

[0037] Therefore, the additive typically forms a selective protective layer on the lithium chip formation area where the flow of lithium ions concentrates during charge / discharge of a lithium metal battery, and the lithium-repellent long-chain aliphatic hydrocarbon group contained in the protective layer repels lithium ions toward the periphery of the lithium chip, thereby suppressing the rapid growth of needle-like lithium or lithium dendrites from the lithium chip, thereby enabling the overall uniform growth of lithium in the lithium metal thin film anode.

[0038] Furthermore, the cations of the additive have a structure in which identical long-chain aliphatic hydrocarbon groups are bonded in a symmetrical configuration, thereby exhibiting relaxed amphiphilicity and low interaction with the non-aqueous organic solvent contained in the electrolyte. Therefore, unlike the case where an additive having an asymmetric cation is used (see the left side of the lower part of Figure 1), the self-aggregation phenomenon between the cations of the additive is reduced (see the right side of the lower part of Figure 1), resulting in the formation of a uniform protective layer that entirely covers the lithium tip formation area. In contrast, when an additive containing an asymmetric cation is used, the protective layer may not be properly formed in some areas around the lithium tip due to the self-aggregation phenomenon between the cations, and needle-shaped lithium may still grow in those areas.

[0039] Therefore, when a secondary battery such as a lithium metal battery is provided using the additive of the embodiment as an electrolyte, the growth of acicular lithium or lithium dendrites on the lithium metal negative electrode can be minimized, and uniform lithium can be grown on the lithium metal negative electrode during charge / discharge.

[0040] Therefore, a lithium metal battery using the additive of one embodiment can minimize problems such as cell short circuit or ignition due to the growth of acicular lithium or lithium dendrites, and can maintain the high capacity characteristics unique to lithium metal batteries over the long term, thereby exhibiting improved life characteristics.

[0041] Meanwhile, in one embodiment of the additive, the cation may have a standard reduction potential of −3.7 V to −3.1 V, −3.65 V to −3.15 V, or −3.6 V to −3.3 V relative to the standard hydrogen electrode. These standard reduction potentials may be calculated based on the reduction potential of the standard hydrogen electrode, 0 V. By using an ionic liquid compound additive containing a cation having such a standard reduction potential, the additive cation preferentially binds to the lithium tip formation portion over lithium ions during charge / discharge of the lithium metal battery, forming a selective protective layer, thereby more effectively suppressing the growth of needle-like lithium. Furthermore, the standard reduction potential further suppresses decomposition of the cation during battery operation.

[0042] In one embodiment of the additive, the cation has a self-diffusivity of 15*10 calculated by the Stejskal-Tanner equation of the following Equation 1 using the analysis results of Pulsed Field Gradient-NMR (PFG-NMR): -11 m 2 .s -1 Or 30*10 -11 m 2 .s -1 , or 18*10 -11 m 2 .s -1 Or 28*10 -11 m 2 .s -1 , or 20*10 -11 m 2 .s -1 Or 25*10 -11 m 2 .s -1 The hydrodynamic diameter at an absolute temperature of 298K, calculated by the Stockes-Einstein equation of Equation 2 using the PFG-NMR analysis results, can be 1.5 to 3.0 nm, or 1.8 to 2.8 nm, or 2.0 to 2.5 nm.

[0043] [Formula 1]

number

number

[0044] In Equations 1 and 2, E denotes the signal attenuation ratio, γ denotes the gyromagnetic ratio, g denotes the gradient strength, δ (ms) denotes the duration pulse, Δ (ms) denotes the gradient pulse interval, D denotes the self-diffusivity, d denotes the hydrodynamic diameter, and k denotes the hydrodynamic diameter. B denotes the Boltzmann constant, T denotes the absolute temperature (for example, the measurement temperature of 298 K), and η denotes the viscosity of the solvent.

[0045] The self-diffusivity and hydrodynamic diameter are properties that can be calculated from the parameters derived from PFG-NMR analysis of the cations of the ionic liquid compound using Equations 1 and 2. These properties can reflect the interactivity, diffusibility, or self-aggregation of the cations with respect to non-aqueous organic solvents.

[0046] Specifically, the additive cation of one embodiment has a symmetric structure in which the same long-chain aliphatic hydrocarbon groups, e.g., the same long-chain linear alkyl groups, are bonded to each other, and thus can have a larger self-diffusivity and a smaller hydrodynamic diameter than additive cations having an asymmetric structure. This may indicate that the additive cation of one embodiment has relatively low amphiphilicity, e.g., low interaction with the non-aqueous organic solvent contained in the electrolyte.

[0047] 1, an additive having such a symmetrical cation structure according to one embodiment has a low tendency to self-aggregate around lithium chips or protrusions, and can be uniformly adsorbed or bonded to the lithium chips to form a protective layer that selectively and uniformly surrounds the lithium chips. Therefore, the use of such an additive can more effectively suppress the growth of needle-like lithium or lithium dendrites from the lithium chips.

[0048] To effectively exhibit the above-mentioned properties, the long-chain aliphatic hydrocarbon group bonded to the cation may be an alkyl group having 3 or more carbon atoms, or 3 to 20 carbon atoms, or 4 to 15 carbon atoms, or 5 to 10 carbon atoms, more suitably a straight-chain alkyl group having such carbon atoms, and an even number of such hydrocarbon groups may be bonded to the central element of the cation, so that the cation has a symmetrical structure. Therefore, the growth of needle-like lithium from the lithium chips can be more effectively suppressed.

[0049] Meanwhile, according to a specific example, the ionic liquid compound of the additive may be represented by the following Chemical Formula 1, and more specifically, may be represented by the following Chemical Formula 2.

[0050] [Chemical formula 1] [ka] In the above Chemical Formula 1, [ka] represents a nitrogen-containing heterocycle having 3 to 8 carbon atoms, or 4 to 7 carbon atoms, or 5 to 6 carbon atoms; the R1s each represent the same linear alkyl group having 3 to 20 carbon atoms, or 4 to 15 carbon atoms, or 5 to 10 carbon atoms; A - indicates an anion.

[0051] [Chemical formula 2] [ka] In Formula 2, R1 represents the same linear alkyl group having 3 to 20 carbon atoms, or 4 to 15 carbon atoms, or 5 to 10 carbon atoms; A - indicates an anion.

[0052] Specific examples of the additive represented by the formula 1 or 2 include 1,1-dihexylpyrrolidium cation (Pyr6(6) + ) or 1,1-dipropylpyrrolidium cation, etc., as described below, anion A - and ionic liquid compounds bonded to

[0053] As will be seen in the following examples, these compounds contain long, linear alkyl groups symmetrically bonded to pyrrolidinium cations, which allows them to form a highly uniform and selective protective layer on the lithium tip formation portion of the lithium metal thin film, effectively inhibiting the growth of acicular lithium or lithium dendrites and enabling uniform lithium growth from the lithium metal negative electrode. Among these compounds, Pyr6(6) is preferred for more effectively inhibiting the growth of acicular lithium. + As shown in the following, an ionic liquid compound containing a pyrrolidium cation to which linear alkyl groups having 4 or more, 5 or more, or 5 to 15 carbon atoms are symmetrically bonded can be preferably used.

[0054] Meanwhile, the additive compound such as Formula 2 can be prepared by alkylating pyrrolidine with R1-X (R1 is as defined in Formula 2, and X is a halogen) in the presence of a base such as potassium carbonate to form a compound of Formula 2A, and then reacting the compound of Formula 2A with LiA (A is as defined in Formula 2).

[0055] [Chemical formula 2A] [ka]

[0056] In Formula 2A, R1 is as defined in Formula 2; - indicates a halogen anion.

[0057] In the additive according to the embodiment described above, the anion bonded to the cation is not particularly limited as long as the additive can become an ionic liquid compound at atmospheric pressure and at 100°C or less and can be included as an additive in the electrolyte of a lithium metal battery, etc. However, from the viewpoint of forming a more stable solid electrolyte interphase (SEI) film on the thin lithium metal film constituting the negative electrode of a lithium metal battery, the anion is preferably a fluorine-containing anion, more specifically, a bis(fluorosulfonyl)imide (FSI) anion, a bis((trifluoromethyl)sulfonyl)imide (TFSI) anion, a hexafluorophosphate (PF6) anion, or a difluoro(oxalato)borate (DFOB) anion.

[0058] When an ionic liquid compound having such an anion is used as an electrolyte additive, the excellent ionic conductivity of a lithium metal battery is maintained, while a more stable SEI film, such as an SEI film containing lithium fluoride (LiF) or lithium nitride (LiN), can be formed on the negative electrode through a reaction between the electrolyte and the lithium metal negative electrode, thereby more effectively suppressing the growth of acicular lithium or lithium dendrites.

[0059] The additive of the above-described embodiment is preferably used as an additive in an electrolyte of a lithium metal battery, for example, an electrolyte solution containing a lithium salt and a non-aqueous organic solvent, and can effectively inhibit the growth of acicular lithium or lithium dendrites at the negative electrode of the lithium metal battery, making the growth of lithium uniform at the negative electrode, and greatly improving the safety and life characteristics of the lithium metal battery.

[0060] Meanwhile, the category of lithium metal batteries in which the additive of an embodiment can be used may include not only general lithium metal batteries manufactured by forming a lithium metal thin film on a negative electrode current collector, but also so-called lithium-free batteries manufactured without forming a separate lithium metal thin film or a negative electrode active material layer on a negative electrode current collector.

[0061] In such lithium-free batteries, lithium metal grown on the negative electrode current collector during charge / discharge can act as a negative electrode active material. In such lithium-free batteries, the additive also forms a protective layer on the lithium metal acting as the negative electrode active material, thereby effectively suppressing the uneven growth of acicular lithium or lithium dendrites.

[0062] According to another embodiment of the present invention, there is provided a lithium metal battery including the additive. The lithium metal battery may include an anode including a lithium metal thin film formed on an anode current collector, an electrolyte including the additive, and a cathode including a cathode active material layer formed on a cathode current collector.

[0063] In this lithium metal battery, a protective layer containing the additive cations can be further formed on the lithium metal thin film as the charge / discharge process progresses. In particular, this protective layer can be formed to selectively cover the lithium chips or protrusions (needle-shaped lithium growth portions) of the lithium metal thin film where the electric field and lithium ion flow are concentrated during charge / discharge. Within this protective layer, the additive cations can be evenly adsorbed or bound to the lithium metal thin film at the needle-shaped lithium growth portions (lithium chip formation portions) without self-aggregation.

[0064] In addition, an SEI film may be further included which is formed on the lithium metal thin film by the reaction of the anions of the additive with the lithium metal. Such an SEI film may contain lithium fluoride (LiF) and / or lithium nitride (LiN) as a main component, with the lithium ions and fluorine and / or nitrogen derived from the anions of the additive being combined.

[0065] Such an SEI coating and protective layer can suppress excessive growth of needle-like lithium from the lithium metal thin film and the resulting fire or cell short circuit, thereby allowing the lithium metal battery of other embodiments to exhibit improved safety and life characteristics.

[0066] Meanwhile, the lithium metal battery of the other embodiment may follow the configuration of a general lithium metal battery, except for the use of the electrolyte additive, etc. Additional configurations of such a lithium metal battery will be described below.

[0067] The lithium metal battery according to the above-described embodiment includes a lithium metal thin film formed on a negative electrode current collector as a negative electrode. In this case, the negative electrode current collector may be any metal current collector, typically a metal current collector such as copper or aluminum.

[0068] Such a metal current collector may be formed to a thickness of typically 3 to 500 μm. The lithium metal thin film formed on the metal current collector may be formed to a thickness of 1 to 100 μm, 5 to 80 μm, or 10 to 60 μm, depending on the typical configuration of a lithium metal battery. The lithium metal thin film may be formed on the metal current collector by a method well known in the art, such as deposition, electroplating, or rolling.

[0069] On the other hand, the electrolyte of the lithium metal battery may be an electrolytic solution (liquid electrolyte) containing a non-aqueous organic solvent and a lithium salt.

[0070] In this case, the non-aqueous organic solvent dissolves the lithium salt and additives and acts as a medium through which ions involved in the electrochemical reaction of the battery can move.

[0071] The type of the non-aqueous organic solvent is not particularly limited, and an ether-based, carbonate-based, ester-based, ketone-based, alcohol-based or aprotic solvent may be used. Examples of the carbonate solvent that may be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (EMC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). Examples of the ester solvent that may be used include methyl acetate, ethyl acetate, n-propyl acetate, 1,1-dimethylethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, and caprolactone. Examples of the ether-based solvent include dimethyl ether, 1,2-dimethoxyethane (1,2-DIMETHOXYETHANE), dibutyl ether, tetraglyme, diglyme, 2-methyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone-based solvent include cyclohexanone. Examples of the alcohol-based solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include tolyls such as R-CN (where R is a C2 to C20 linear, branched, or cyclic hydrocarbon group that may contain a double bond-oriented ring or ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, ether-based solvents or carbonate-based solvents can be used appropriately from the viewpoint of improving the life characteristics of lithium metal batteries.

[0072] In addition, the non-aqueous organic solvents may be used alone or in combination of two or more. When two or more organic solvents are used in combination, the mixing ratio can be appropriately adjusted depending on the desired battery performance, which should be widely understood by those skilled in the art.

[0073] In addition, in the case of the carbonate-based solvent, it is preferable to use a mixture of cyclic carbonate and chain carbonate in a volume ratio of about 1:1 to about 1:9, which can provide excellent electrolyte performance.

[0074] The non-aqueous organic solvent may further include the aromatic hydrocarbon organic solvent in addition to the carbonate solvent, and the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.

[0075] Examples of the aromatic hydrocarbon organic solvent include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, Ene, fluorotoluene, 1,2-difluorotoluene, 1,3-difluorotoluene, 1,4-difluorotoluene, 1,2,3-trifluorotoluene, 1,2,4-trifluorotoluene, chlorotoluene, 1,2-dichlorotoluene, 1,3-dichlorotoluene, 1,4-dichlorotoluene, 1,2,3-trichlorotoluene, 1,2,4-trichlorotoluene, iodotoluene, 1,2-diiodotoluene, 1,3-diiodotoluene, 1,4-diiodotoluene, 1,2,3-triiodotoluene, 1,2,4-triiodotoluene, xylene or combinations thereof may be used.

[0076] The non-aqueous organic solvent may further contain a vinylene carbonate or ethylene carbonate compound to improve battery life.

[0077] Representative examples of the ethylene carbonate-based compound include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. When vinylene carbonate or the ethylene carbonate-based compound is further used, the amount used can be appropriately adjusted to improve the lifespan.

[0078] In the electrolyte of the lithium metal battery, the lithium salt dissolves in the organic solvent and acts as a source of lithium ions, enabling the basic operation of the lithium metal battery of the other embodiment and promoting the movement of lithium ions between the positive electrode and the negative electrode.

[0079] The lithium salt may be any lithium salt that is generally widely used as an electrolyte. For example, lithium bis(fluorosulfonyl)imide (LiFSI) or lithium bis((trifluoromethyl)sulfonyl)imide (LiTFSI) may be used. In addition, LiPF, LiBF, LiSbF, LiAsF, LiC, F, SO, LiClO, LiAlO, LiAlCl, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (where x and y are natural numbers), LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato)borate; LiBOB), or a combination thereof may be used.

[0080] The concentration of the lithium salt in the electrolyte may be controlled within a range of 0.1 to 5.0 M. Within this range, the electrolyte may have appropriate conductivity and viscosity, allowing lithium ions to move effectively within the lithium metal battery. However, this is merely an example and is not intended to limit the scope of the invention.

[0081] The electrolyte may be impregnated in a porous separator located between the negative electrode and the positive electrode. The porous separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move, and any porous separator commonly used in lithium secondary batteries may be used. That is, a porous separator having low resistance to ion movement of the electrolyte and excellent humidifying ability for the electrolyte solution may be used.

[0082] For example, the separator may be made of glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), or a combination thereof, and may be in the form of a nonwoven or woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are commonly used, and to ensure heat resistance or mechanical strength, separators coated with ceramic components or polymer materials may be used, and may be selectively used in a single-layer or multi-layer structure.

[0083] The lithium metal battery further includes a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.

[0084] In this case, the positive electrode active material layer may be manufactured by mixing the positive electrode active material and a binder, and optionally a conductive material and a filler, in a solvent to prepare a positive electrode mixture in a slurry state, and then applying the positive electrode mixture to a positive electrode current collector. Such a positive electrode manufacturing method is widely known in the art, and therefore a detailed description thereof will be omitted here.

[0085] The positive electrode active material is not particularly limited as long as it is a material that allows reversible insertion and desorption of lithium ions, and may include, for example, one or more of a composite oxide of lithium and cobalt, manganese, nickel, iron, aluminum, or a combination of at least one of these metals.

[0086] More specifically, the positive electrode active material may be a compound represented by any one of the following chemical formulas: Lia A 1-b R b D2 (wherein, in the above formula, 0.90≦a≦1.8 and 0≦b≦0.5); Li a E 1-b R b O 2-c D c (wherein 0.90≦a≦1.8, 0≦b≦0.5, and 0≦c≦0.05); LiE 2-b R b O 4-c D c (wherein 0≦b≦0.5 and 0≦c≦0.05); Li a Ni 1-b-c Co b R c D α (wherein 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Co b R c O 2-α Z α (wherein 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Co b R c O 2-α Z2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b R c D α (wherein 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b R c O 2-α Z α (wherein 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b R c O 2-αZ2 (wherein, 0.90≦a≦1.8, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O2 (wherein 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, and 0.001≦d≦0.1 in the above formula); Li a Ni b Co c Mn d G e O2 (wherein 0.90≦a≦1.8, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, and 0≦e≦0.1 in the above formula); Li a NiG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); Li a CoG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); Li a MnG b O2 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); Li a Mn2G b O4 (wherein 0.90≦a≦1.8 and 0.001≦b≦0.1 in the above formula); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f) Fe2(PO4)3(0≦f≦2); LiFePO4.

[0087] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.

[0088] Among these various active materials, positive electrode active materials that exhibit high capacity characteristics and require a high level of safety, such as Li with a high Ni content, a Ni b’ Co c Mn d G e The positive electrode active material can be preferably applied to lithium metal batteries of different embodiments, such as O2 (wherein 0.90≦a≦1.8, 0.4≦b′≦0.95, 0≦c≦0.5, 0≦d≦0.5, and 0≦e≦0.1, and G is Al) or LiFePO4.

[0089] The above-mentioned positive electrode active materials may have a coating layer on the surface of each compound, or may be a mixture of the above-mentioned compounds and compounds having a coating layer. The coating layer may be a coating element compound, such as an oxide, hydroxide, oxyhydroxide, oxycarbonate, or hydroxycarbonate of the coating element. The compounds forming these coating layers may be amorphous or crystalline. The coating elements contained in the coating layer may be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or mixtures thereof. The coating layer formation process may be performed using any coating method (e.g., spray coating, dipping, etc.) that can coat the compound with such elements without adversely affecting the physical properties of the positive electrode active material. This is well understood by those skilled in the art, so a detailed description will be omitted.

[0090] Meanwhile, the positive electrode current collector is generally formed to a thickness of 3 to 500 μm. Such a positive electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be made of, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The current collector may have fine irregularities on its surface to enhance adhesion of the positive electrode active material, and may be in various forms such as a film, sheet, foil, net, porous material, foam, or nonwoven fabric.

[0091] The conductive material is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and examples thereof include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskey such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0092] The lithium metal battery of the embodiment may be used not only as a unit cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a number of battery cells. Furthermore, a battery pack including the battery module may be constructed.

[0093] The following describes preferred embodiments of the present invention, comparative examples for comparison, and experimental examples for evaluating these. However, the following examples are merely preferred embodiments of the present invention, and the present invention is not limited to the following examples.

[0094] Example 1: Electrolyte Additive (1,1-dihexylpyrrolidium bis(fluorosulfonyl)imide, Pyr6(6) + FSI - ) synthesis A round-bottom flask was charged with 50 mL of acetonitrile, pyrrolidine (3.56 g, 50 mmol), and potassium carbonate (7.60 g, 55 mmol). 1-Bromohexane (24.76 g, 150 mmol) was slowly added to the mixture, and the mixture was stirred at 65 °C for 8 hours. The solution was then filtered, and the solvent was removed from the filtrate under reduced pressure. The residue was washed with hexane to obtain 1,1-dihexylpyrrolidium bromide [Pyr6(6)Br] as a yellow solid.

[0095] After drying this Pyr6(6)Br under vacuum at 80 °C for 10 hours, the same moles of Pyr6(6)Br and LiFSI were dissolved in 20 mL of acetonitrile and stirred at room temperature for 5 hours. The solution was then evaporated under reduced pressure, and 10 mL of dichloromethane was added to the concentrated product. The mixture was then filtered and extracted with water, and excess salt was removed from the filtrate. The lower organic phase was collected and rotary evaporated to remove the solvent. This sample was placed under vacuum at 80 °C for 10 hours to obtain Pyr6(6). + FSI - The additive was finally produced as an orange liquid.

[0096] Comparative Example 1: In the following description, a case in which no electrolyte additive was used is referred to as Comparative Example 1.

[0097] Comparative Example 2: Electrolyte Additive (1-dodecyl-1-methylpyrrolidium bis(fluorosulfonyl)imide, Pyr1(12) + FSI - ) synthesis A round-bottom flask was charged with 50 mL of acetonitrile and 1-methylpyrrolidine (4.26 g, 50 mmol). 1-Bromododecane (14.95 g, 60 mmol) was slowly added to the mixture, and the mixture was stirred at 65 °C for 8 hours. The solution was then filtered, and the solvent was removed from the filtrate under reduced pressure. The residue was washed with hexane to obtain 1-dodecyl-1-methylpyrrolidium bromide [Pyr1(12)Br] as a yellow solid.

[0098] After drying this Pyr1(12)Br under vacuum at 80 °C for 10 hours, the same moles of Pyr1(12)Br and LiFSI were dissolved in 20 mL of acetonitrile and stirred at room temperature for 5 hours. The solution was then evaporated under reduced pressure, and 10 mL of dichloromethane was added to the concentrated product. The mixture was then filtered and extracted with water, and excess salts were removed from the filtrate. The lower organic phase was collected and rotary evaporated to remove the solvent. This sample was then placed under vacuum at 80 °C for 10 hours to obtain Pyr1(12). + FSI - The additive was finally manufactured into a clear liquid.

[0099] Experimental Example 1: Measurement of self-diffusivity and hydrodynamic diameter of additives The additives of Example 1 and Comparative Example 2 were analyzed using a liquid (400 MHz) NMR analyzer (Bruker). 1 H - , 7 Li - , and 19 Based on the analysis results, the self-diffusivity of the cations of the additives was calculated by applying the Stejskal-Tanner equation shown in Equation 1 below.

[0100] Furthermore, based on the NMR analysis results and the self-diffusivity calculation results, the hydrodynamic diameter of each of the additive cations at an absolute temperature of 298 K was calculated by applying the Stockes-Einstein equation of the following Equation 2:

[0101] [Formula 1]

number

number

[0102] In Equations 1 and 2, E denotes the signal attenuation ratio, γ denotes the gyromagnetic ratio, g denotes the gradient strength, δ (ms) denotes the duration pulse, Δ (ms) denotes the gradient pulse interval, D denotes the self-diffusivity, d denotes the hydrodynamic diameter, and k denotes the hydrodynamic diameter. B denotes the Boltzmann constant, T denotes the absolute temperature (=298K), and η denotes the viscosity of the solvent.

[0103] For your reference, the NMR analysis results are as follows: 1 H-NMR δ(ms)=3.6, Δ(ms)=80-150, 7 Li-NMR δ(ms)=4.0, Δ(ms)=300-400, 19 For F-NMR, δ(ms)=2.5-3.2, Δ(ms)=300-500.

[0104] The physical properties analyzed and calculated by the above-mentioned methods are shown in Table 1 below.

[0105] [Table 1]

[0106] Referring to Table 1 above, it was confirmed that although the additives of Example 1 and Comparative Example 2 contain cations with similar molecular sizes, the additive cation of Example 1 exhibits a larger self-diffusivity and a hydrodynamic diameter that is about 1.6 times smaller than that of Comparative Example 2.

[0107] Based on this, it was confirmed that the additive cation of Example 1 exhibits relaxed amphiphilicity and a low tendency to self-aggregate, which is advantageous for forming a uniform protective layer surrounding the lithium chip.

[0108] Experimental Example 2: Evaluation of the surface properties of lithium metal thin films after lithium metal deposition An electrolyte was prepared by dissolving the lithium salt of lithium bis(trifluoromethyl)sulfonyl)imide (LiTFSI) in a mixed solvent of 1,3-dioxolane / 1,2-dimethoxyethane (DOL / DME - 1:1 (v / v%)) at a concentration of 1 M. This additive-free electrolyte was used as the electrolyte of Comparative Example 1.

[0109] In addition, the additive of Example 1 or the additive of Comparative Example 2 was dissolved in the electrolyte to a concentration of 1M to prepare the electrolytes of Example 1 and Comparative Example 2, respectively.

[0110] Using the electrolytes of Example 1, Comparative Examples 1 and 2, respectively, 0.1 mAh cm -2 Electrolytic plating was carried out under application of a current of 18 μm to deposit a thin film of lithium metal on each copper current collector (thickness: 18 μm).

[0111] After this deposition, the surface conditions of each lithium metal thin film were examined using an electron microscope for Comparative Example 1 (no additive used; Figure 2a), Comparative Example 2 (using Pyr1(12) FSI additive; Figure 2b), and Example 1 (using Pyr6(6) FSI additive; Figure 2c), and are shown in Figures 2a to 2c, respectively.

[0112] Furthermore, from the surface analysis results of the lithium metal thin film, the number and size of lithium chips (protrusions) having a size of about 0.25 μm or more were confirmed, and from these confirmation results, the average protrusion size and standard deviation of the lithium chips were calculated and shown as graphs in the lower part of Figures 2a to 2c.

[0113] 2a to 2c, it was confirmed that when the additive of Example 1 was used, the number and size of protrusions on the lithium metal thin film were reduced, and a lithium metal thin film having a uniform surface was formed over the entire area of ​​the current collector.

[0114] This is presumably because the additive of Example 1 formed a uniform protective layer surrounding the protrusions during lithium deposition, as shown in FIG. 1, thereby inducing uniform lithium deposition and growth.

[0115] Experimental Example 3: Evaluation of the life characteristics of lithium metal batteries LiNi 0.6 Co 0.2 Mn 0.2 The cathode active material was O2 (NCM622). This cathode active material, carbon black conductive material (super-P), and PVdF binder (Mw = 455,000; Sigma-Aldrich) were mixed in N-methylpyrrolidone solvent at a weight ratio of 90:5:5 to prepare a cathode mixture. This mixture was then applied to one side of an aluminum current collector (thickness: 20 μm), dried in a vacuum oven at 110°C, and rolled to prepare a cathode.

[0116] The negative electrode was prepared by forming a lithium metal thin film (thickness: 40 μm) on one surface of a copper current collector (thickness: 18 μm).

[0117] An electrode assembly was prepared by interposing a porous polypropylene separator (Celguard 2325; thickness: 25 μm) between the cathode and anode prepared as described above. The electrode assembly was then placed inside a case, and an electrolyte was injected into the case to prepare a lithium metal battery.

[0118] An electrolyte solution was prepared by dissolving lithium bis(trifluoromethyl)sulfonyl)imide (LiTFSI) in a 1:1 (v / v%) mixed solvent of 1,3-dioxolane / 1,2-dimethoxyethane (DOL / DME) to a concentration of 1 M. The additive of Example 1 or the additive of Comparative Example 2 was added to the electrolyte solution to a concentration of 50 mM, and lithium metal batteries of Example 1 and Comparative Example 2 were prepared depending on the type of additive used in the electrolyte solution.

[0119] Each lithium metal battery was charged at 0.5 C to 4.2 V in CCCV mode at 25°C and then discharged at a constant current of 0.5 C to 3.0 V, and the capacity retention and coulombic efficiency were measured after 250 charge-discharge cycles. The results of the capacity retention and coulombic efficiency measurements are summarized in Table 2 below.

[0120] [Table 2]

[0121] Referring to Table 2 above, it was confirmed that the lithium metal battery using the symmetric cation-containing additive of Example 1 exhibited high capacity retention and coulombic efficiency even after 250 charge / discharge cycles, and exhibited excellent life characteristics.

[0122] However, it was confirmed that the lithium metal battery using the asymmetric cation-containing additive of Comparative Example 2 exhibited inferior capacity retention and life characteristics compared to the Examples. This is presumably because the use of the additive of Comparative Example 2 did not sufficiently suppress the growth of acicular lithium or lithium dendrites, resulting in non-uniform growth of the lithium thin film during charge / discharge.

Claims

1. An additive comprising an ionic liquid compound that exhibits a liquid state containing cations and anions at atmospheric pressure and a temperature of 100° C. or less, The cation is a lithium cation (Li) based on a standard hydrogen electrode (SHE). + ) has a lower standard reduction potential than The cation has an even number of identical aliphatic hydrocarbon groups having 3 or more carbon atoms bonded to a central element, and has a symmetric structure with respect to the central element.

2. 2. The additive for a secondary battery according to claim 1, wherein the cation has a standard reduction potential of −3.7 V to −3.1 V based on a standard hydrogen electrode.

3. The cation has a self-diffusivity calculated by the Stejskal-Tanner equation of 15*10 -11 m 2 .s -1 or 30*10 -11 m 2 .s -1 The secondary battery additive according to claim 1 ,

4. 2. The additive for a secondary battery according to claim 1, wherein the cation has a hydrodynamic diameter of 1.5 to 3.0 nm calculated by the Stockes-Einstein equation at an absolute temperature of 298K.

5. The additive for a secondary battery according to claim 1, wherein the ionic liquid compound is represented by the following chemical formula 1: [Chemical formula 1] 【Chemistry 1】 In the above Chemical Formula 1, 【Chemistry 2】 represents a nitrogen-containing heterocycle having 3 to 8 carbon atoms, each of the R1's represents the same linear alkyl group having 3 to 20 carbon atoms, A - indicates an anion.

6. The additive for a secondary battery according to claim 5, wherein the ionic liquid compound is represented by the following chemical formula 2: [Chemical formula 2] 【Chemistry 3】 In Formula 2, R1 represents the same linear alkyl group having 3 to 20 carbon atoms; - indicates an anion.

7. 2. The secondary battery additive according to claim 1, wherein the anion is selected from the group consisting of fluorine-containing anions.

8. The anion may be a bis(fluorosulfonyl)imide (FSI) anion, a bis((trifluoromethyl)sulfonyl)imide (TFSI) anion, or a hexafluorophosphate (PF 6 2. The secondary battery additive according to claim 1, comprising a difluoro(oxalato)borate (DFOB) anion or a difluoro(oxalato)borate (DFOB) anion.

9. The secondary battery additive according to claim 1, which is used in an electrolyte of a lithium metal battery.

10. a negative electrode including a lithium metal thin film formed on a negative electrode current collector; An electrolyte comprising the additive according to any one of claims 1 to 8; a positive electrode including a positive electrode active material layer formed on a positive electrode current collector.

11. 11. The lithium metal battery of claim 10, further comprising a protective layer formed on the lithium metal thin film and comprising a cation of the additive.

12. 12. The lithium metal battery of claim 11, wherein the additive cations selectively cover the acicular lithium protruding from the lithium metal thin film.

13. 11. The lithium metal battery of claim 10, further comprising a solid electrolyte interphase (SEI) film formed on the lithium metal thin film.

14. The solid electrolyte interface film is made of lithium fluoride (LiF) or lithium nitride (Li 3 14. The lithium metal battery of claim 13 comprising:

15. 11. The lithium metal battery according to claim 10, wherein the positive electrode active material layer contains a composite oxide of lithium and a metal selected from the group consisting of cobalt, manganese, nickel, iron, aluminum and a combination of at least one of these.

16. The electrolyte includes lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis((trifluoromethyl)sulfonyl)imide (LiTFSI), LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiC 4 F 9 SO 3 , LiClO 4 , LiAlO 2 , LiAlCl 4 , LiN (C x F 2x+1 SO 2 ) (C y F 2y+1 SO 2 ) (x and y are each independently a natural number), LiCl, LiI and LiB (C 2 O 4 ) 2 One or more lithium salts selected from the group consisting of 13. The lithium metal battery of claim 12, further comprising a non-aqueous organic solvent.

Citation Information

Patent Citations

  • Gel type ionic liquid electrolyte for lithium ion battery as well as preparation method and application thereof

    CN111653822A

  • Electrochemical device for use at high temperatures

    JP2007517364A

  • Lithium metal battery

    US20170098858A1

  • Secondary battery

    WO2009142251A1

  • Solid electrolyte, electrode, power storage element, and method for producing solid electrolyte

    WO2021241002A1